The Long-Term Outcomes of Wait-and-Scan and the Role of Radiotherapy in the Management of Vestibular Schwannomas. Issue 4 (April 2015) - Patnaik, Uma; Prasad, Sampath Chandra; Tutar, Hakan; Giannuzzi, Anna Lisa; Russo, Alessandra; Sanna, Mario
Abstract : Objective: To analyze the growth characteristics in patients assigned to wait and scan in vestibular schwannomas (VSs) during long-term follow-up. Background: The wait-and-scan policy and radiotherapy (RT) are conservative management strategies for VSs. A better insight into the natural history of the tumor and growth patterns is quintessential in planning optimal management. Methods: The charts of 576 patients with unilateral sporadic VSs who were assigned to wait and scan at our center from 1986 to 2013 were reviewed. A systematic review of radiosurgical literature was done and compared with results of wait and scan. Results: The overall mean follow-up was 36.9 ± 30.2 months. One hundred fifty-four patients with a 5-year follow-up were analyzed separately for patterns of tumor growth. Varied combinations of growth patterns were observed. Eighty-four (54.5%) tumors showed no growth throughout 5 years, 12 (7.8%) showed slow growth throughout 5 years, 2 (1.3%) tumors showed fast growth throughout 5 years. A total of 134 tumors (87%) showed favorable growth patterns for wait and scan. When the results of wait and scan were compared with those of RT, it pointed to the possibility that at least a portion of control of tumor by RT could be attributed to the natural course of the tumor. Conclusion: The wait-and-scan modality is ideal for management of VSs in the elderly population and also in younger patients with intrameatal tumors. Considering the fact that a large percentage of tumors do not require any form of treatment, the role of RT in VSs needs to be reinvestigated.